Quantum chemical computational studies of 1, 3-diammonium propylarsenate: a semi organic crystalline salt. Issue 10 (3rd October 2022) - Senthilkumar, K.; Kanagathara, N.; Ragavendran, V.; Natarajan, V.; Marchewka, M.K.
Abstract: A semi organic crystalline salt − 1, 3–diammonium propylarsenate (1-3-DAPAS) has been introduced for experimental and theoretical investigation. Gaussian 09 program has been utilized to quantify the quantum chemical theoretical estimations. DFT/B3LYP-6-311++G(d, p) procedure is accustomed to enhance the structure. Molecular structural and vibrational characterization have been carried out and their experimental and theoretical results were correlated. Natural bonding orbital scrutiny and frontier molecular orbital probe endorsed the charge transfer apart from the presence of strong inter and intra molecular interactions. First order hyperpolarizability is computed to study the microscopic behavior of the synthesized compound (1-3-DAPAS). It is calculated from first order hyperpolarizability that 1-3-DAPAS is 7.3246 times that of urea and may be expected potential candidate for the development of NLO materials.